Arrivals of Foreigners to Poland with Particular Emphasis on Visitors from Outside the Schengen Area – Characteristics and Prospects for the Future - Łukasiewicz, Katarzyna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
Poland is very popular among foreigners. Tourism is an important part of the Polish economy. The share of tourism in GDP remains at a level of 5-6%, with employment estimated at approx. 760 thousand. People (4.7% of the total workforce), with approx. 170-200 thousand. People are employed in activities related to accommodation and food service. Proceeds from the arrivals of foreigners goes back to the year 8-9 billion euros, of which about half is the proceeds of arrivals of foreign tourists. The aim of the article is to present the characteristics of arrivals of foreigners to Poland, with particular emphasis on visitors from outside the Schengen Area. On the basis of statistical data I analysed arrivals of foreign tourists to Poland and presented the changes in the structure of those arrivals. The article also shows the diversity of tourism revenue in the period considered. For this purpose a method of "Desk Research" based on data from Central Statistical Office, Institute of Tourism, Ministry of Sport and Tourism. The article also includes the perspective of the development of inbound tourism. The article presents the results of research conducted in October 2016 in Kiev among 152 respondents. The aim of the study was to collect the information on the attractiveness of Poland for Ukrainian visitors. Convenient sampling method was used to select the survey participants. Diagnostic survey method was used in the study and the direct technique was an interview without previously prepared questions. The results confirm that Ukrainians are willing to visit Poland.